WHEN DOES THE BOMBIERI–VINOGRADOV THEOREM HOLD FOR A GIVEN MULTIPLICATIVE FUNCTION?. (24th August 2018) - GRANVILLE, ANDREW; SHAO, XUANCHENG
Abstract : Let f and g be 1-bounded multiplicative functions for which f* g=1_.=1 . The Bombieri–Vinogradov theorem holds for both f and g if and only if the Siegel–Walfisz criterion holds for both f and g, and the Bombieri–Vinogradov theorem holds for f restricted to the primes.